Single-direction thoracoscopic lobectomy: a step in the right direction - Young, John S.; Lee, Paul C. (Journal of Thoracic Disease, 2019)
Thoracoscopy in the treatment of thoracic disease is not a recent phenomenon. As early as 1910, Jacobaeus et al. examined the thoracic cavity and pleura with a cystoscope (1). The thoracoscope’s role was in management of pleural disease or for limited lung biopsies.